Peran Pengendalian Internal dan Good Governance Terhadap Peningkatan Pegawai di Dinas Lingkungan Hidup Provinsi Jawa Timur - Nadia Farah Nafisa; Hero Priono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Along with the development of public knowledge about the implementation of government, the government must be able to carry out implementation properly. The government is tasked with providing services to improve the welfare of the people with a fair, good, and accountable system. This study was conducted with the aim of knowing the effect of internal control and implementation of good governance on employee performance. This type of quantitative research with a sample used 85 employees of the Environmental Service. This research utilizes purposive sampling method. The data analysis technique applied is multiple linear regression analysis. The findings of this study prove that internal control has a significant effect on employee performance, while good governance has no effect.